2014
DOI: 10.1073/pnas.1320924111
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zone CD169+macrophages coordinate apoptotic cell-driven cellular recruitment and tolerance

Abstract: Tolerance to apoptotic cells is essential to prevent inflammatory pathology. Though innate responses are critical for immune suppression, our understanding of early innate immunity driven by apoptosis is lacking. Herein we report apoptotic cells induce expression of the chemokine CCL22 in splenic metallophillic macrophages, which is critical for tolerance. Systemic challenge with apoptotic cells induced rapid production of CCL22 in CD169 + (metallophillic) macrophages, resulting in accumulation and activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
116
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 38 publications
4
116
0
Order By: Relevance
“…Given that GCN2 fl LysM cre mice showed abrogated suppression of inflammatory immunity to apoptotic cells, we reasoned that long-term tolerance would be compromised as well. To test this, we used a model of female recognition to male H-Y antigen, in which exposure to male apoptotic cells leads to long-term tolerance to male skin grafts (7,16). In agreement with our previous studies, control groups of female mice rejected male skin, with a mean graft survival time of 26 d; in contrast, female mice receiving a single injection of male apoptotic cells before skin engraftment showed tolerance with no graft rejection (Fig.…”
Section: Gcn2 Is Required For Apoptotic Cell-driven Tolerogenic Immunsupporting
confidence: 81%
See 3 more Smart Citations
“…Given that GCN2 fl LysM cre mice showed abrogated suppression of inflammatory immunity to apoptotic cells, we reasoned that long-term tolerance would be compromised as well. To test this, we used a model of female recognition to male H-Y antigen, in which exposure to male apoptotic cells leads to long-term tolerance to male skin grafts (7,16). In agreement with our previous studies, control groups of female mice rejected male skin, with a mean graft survival time of 26 d; in contrast, female mice receiving a single injection of male apoptotic cells before skin engraftment showed tolerance with no graft rejection (Fig.…”
Section: Gcn2 Is Required For Apoptotic Cell-driven Tolerogenic Immunsupporting
confidence: 81%
“…We previously reported that apoptotic cell-associated antigens fail to induce adaptive T-cell responses (4,6,7). This effect is dependent on IDO1 expression and MZ MΦs, given that Ido1 −/− mice or mice depleted of MZ MΦs showed vigorous T-cell responses to apoptotic cells (6).…”
Section: Gcn2 Is Required For Apoptotic Cell-driven Tolerogenic Immunmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Moreover, recognition and engulfment of AC by macrophages and DC serves to sustain immune tolerance to self-antigens by virtue of the anti-inflammatory cytokines IL-10 and TGF-β released from these cells, and the recruitment of natural regulatory T cells. [4][5][6][7] Post AC engulfment, macrophages appear to be capable of fully digesting AC-associated antigens and limit their access to antigen presentation compartments, and therefore are inefficient at T-cell priming. 8 In contrast, DC are highly efficient at processing and presentation of engulfed antigens, using either direct or cross-presentation pathways, which either anergizes or activates potentially self-reactive T cells, depending on the context of antigen presentation.…”
mentioning
confidence: 99%